Smart cities: Disaster Resilience Outlook in the city Juiz de Fora / MG - dos Santos, Rosana Campos; Rodrigues da Silva Oliveira, Amanda; de Athayde Salomão, Mariana; Alberto Barroso Castañon, José (National Journal of City Management, 2022)
Disasters are phenomena such as: floods, landslides, droughts, hurricanes, earthquakes, among others. Risk and disaster management is a social process that aims to reduce and permanently control the main factors that cause disasters in society. According to the UN (2021), in the last two decades floods were responsible for over 40% of disasters, negatively impacting 1.65 billion people, followed by major storms representing 28%, earthquakes 8% and extreme temperatures 6%. This paper uses as methodology qualitative and exploratory research, followed by literature review, to map the landscape of disaster resilience in Juiz de Fora/MG. Urbanization is a global challenge, in 30 years two thirds of the world’s population will reside in urban areas, so it is essential that cities adapt to be resilient, to preserve life and the environment